Anatomy of the Medial Meniscotibial Ligament of the Knee: A Systematic Review - Jonatas Brito de Alencar Neto; Amanda Progênio dos Santos; Márcio Bezerra Gadelha Lopes; Lana Lacerda de Lima; Renata Clazzer; Diego Ariel de Lima (Revista Brasileira de Ortopedia, 2023)
Abstract Objectives To perform a systematic review of the literature on the anatomy of the medial meniscotibial ligaments (MTLs), and to present the most accepted findings, as well as the evolution of the anatomical knowledge on this structure. Materials and Methods An electronic search was conducted in the MEDLINE/PubMed, Google Scholar, EMBASE and Cochrane library databases with no date restrictions. The following index terms were used in the search: anatomy AND meniscotibial AND ligament AND medial. The review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We included anatomical studies of the knee were included, such as cadaver dissections, histological and/or biological investigations, and/or imaging of the medial MTL anatomy. Results Eight articles that met the inclusion criteria were selected. The first article was published in 1984 and the last, in 2020. The total sample in the 8 articles was of 96 patients. Most studies are purely descriptive in terms of the macroscopic morphological and microscopic histological findings. Two studies evaluated the biomechanical aspects of the MTL, and one, the anatomical correlation with the magnetic resonance imaging examination. Conclusion The main function of the medial MTL, a ligament that originates in the tibia and is inserted in the lower meniscus, is to stabilize and maintain the meniscus in its position on the tibial plateau. However, there is a limited amount of information regarding medial MTLs, primarily in terms of anatomy, especially vascularization and innervation.